Double spikes to single electrical stimulation correlates to spontaneous activity of nociceptors in painful neuropathy patients - Schmidt, Roland; Obreja, Otilia; Schmelz, Martin (Pain, 2012)
Spontaneously active C nociceptors in painful neuropathy patients reveal multiple firing to single electrical stimuli, suggesting that axonal hyperexcitability contributes to neuropathic pain. Multiple firing of C nociceptors upon a single electrical stimulus has been suggested to be a possible mechanism contributing to neuropathic pain. Because this phenomenon maybe based on a unidirectional conduction block, it might also be related to neuropathic changes without a direct link to pain. We investigated painful neuropathy patients using microneurography and analysed nociceptors for the occurrence of multiple spiking and spontaneous activity. In 11 of 105 nociceptors, double spiking was found, with 1fibre even showing triple spikes on electrical stimulation. The interval between the main action potential and the multiple spikes ranged from 13 to 100 ms. There was a significant association between spontaneous activity and multiple spiking in C nociceptors, with spontaneous activity being present in 9 of 11 fibres with multiple spiking, but only in 21 of 94 nociceptors without multiple spiking (P < .005, Fisher exact test). Among the 75 C nociceptors without spontaneous activity, only 2 nociceptors showed multiple spiking. In 8 neuropathy patients without pain, double spiking was found only in 4 of 90 nociceptors. Multiple spiking of nociceptors coincides with spontaneous activity in nociceptors of painful neuropathy patients. We therefore conclude that rather than being a generic sign of neuropathy, multiple spiking is linked to axonal hyperexcitability and spontaneous activity of nociceptors. It is still unclear whether it also is mechanistically related to the clinical pain level.